The Question of Phonetic Balance in Word Recognition Testing - Martin, Frederick N.; Champlin, Craig A.; Perez, Desirée D. (Journal of the American Academy of Audiology, 2000)
Twenty subjects with normal hearing and 15 subjects with mild-to-moderate sensorineural hearing losses were tested with eight lists of words using monosyllabic pronunciation to determine word recognition scores. Four of the lists were taken from Northwestern University Test No. 6 and four were simply made up by randomly selecting words from a dictionary. All of the word lists were used to determine performance-intensity functions. No clinically meaningful differences were observed among the lists.Abbreviations: ANOVA = analysis of variance, NU-6 = Northwestern University Auditory Test No. 6, PB = phonemically/phonetically balanced, SRT = speech recognition threshold, WRS = word recognition score
Keywords: Phonemically balanced word list; phonetically balanced word list; word recognition score